EVALUASI PRESTASI BELAJAR MAHASISWA PROGRAM KELANJUTAN STUDI JURUSAN PENDIDIKAN AKUNTANSI DITINJAU DARI IPK D3 DAN ASAL PERGURUAN TINGGI - M. Djazari; Endra Murti Sagoro (Universitas Negeri Yogyakarta, 2011)
This research examines the difference of students learn performance of cognitive domainpursuant to “IPK D3”, students learn performance of cognitive domain pursuant to comefrom college, students learn performance of affective domain pursuant to “IPK D3”, studentslearn performance of affective domain pursuant to come from college, students learnperformance of psychomotor domain pursuant to “IPK D3”, students learn performance ofpsychomotor domain pursuant to come from college.The subject of this research are 53 respondents. The data were collected by usingquestionnaires and documentation method. The validity of instrument was tested byimplementing construct validity. From computation, one item from learn performance ofaffective domain was not valid and all items from learn of psychomotor domain was valid.The reliability of instrument was tested by implementing the Cronbach Alpha. Fromcomputational, instrument of learn performance of affective domain and psychomotordomain was valid.The test of hypothesis will used Kruskal-Wallis test and Mann-Whitney test. Theresult of the research indicate: (1) there is significantly difference for learning performance ofcognitive domain pursuant to “IPK D3”, (2) there is not significantly difference for learningperformance of cognitive domain pursuant to come from college, (3) there is not significantlydifference for learning performance of affective domain pursuant to “IPK D3”, (4) there isnot significantly difference for learning performance of affective domain pursuant to comefrom college, (5) there is not significantly difference for learning performance ofpsychomotor domain pursuant to “IPK D3, and (6) there is not significantly difference forlearning performance of psychomotor domain pursuant to come from college.Keyword: cognitive domain, affective domain, psychomotor domain